Heart Transplant Survival Outcomes for Adriamycin Dilated Cardiomyopathy - Lenneman, Andrew J. (2012)
In 2015 there will be an estimated 11.3 million cancer survivors. With a growing population of cancer survivors, it is imperative to understand treatment options and outcomes for chemotherapy related cardiomyopathy. Anthracycline (AC) based chemotherapy causes heart failure (HF) in approximately 5% of patients. Orthotopic heart transplant (OHT) is an option for cancer survivors in complete remission who develop end-stage HF. We examined retrospective OHT data collected from United Network of Organ Sharing (UNOS) from 1987–2011. The primary aim to was characterize the survival in patients with either the primary diagnosis of “Dilated Cardiomyopathy: Adriamycin” (DCA) versus “all other” causes of cardiomyopathy. The secondary aim was to define the differences in primary cause of death and to describe the temporal relationship of DCA OHT. The UNOS database identified 453 OHT for the diagnosis of DCA and 51,312 OHT for all other causes of cardiomyopathy. DCA group was significantly younger with a higher percentage of females. After adjusting for age, gender, and previous history of malignancy, the 10-year survival curves show that DCA patients have an improved survival over all other causes cardiomyopathy (HR 1.28, p = 0.026). There was no difference in the primary cause of death between the 2 groups. There was a statistically significant increasing temporal trend in the number of OHT for the diagnosis DCA. In conclusion patients who undergo OHT for DCA have a favorable 10-year survival, making OHT a good therapeutic option for end-stage HF due to anthracyclines. Additionally there was no increased risk of cancer related deaths in the DCA, demonstrating that recurrent malignancy does not impact long-term survival. Temporal trends demonstrate that DCA remains a significant problem for cancer survivors.